2006
DOI: 10.1158/0008-5472.can-06-0418
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fibroblast Growth Factor-Inducible 14 Expression Levels Promote Glioma Cell Invasion via Rac1 and Nuclear Factor-κB and Correlate with Poor Patient Outcome

Abstract: Glial tumors progress to malignant grades by heightened proliferation and relentless dispersion throughout the central nervous system. Understanding genetic and biochemical processes that foster these behaviors is likely to reveal specific and effective targets for therapeutic intervention. Our current report shows that the fibroblast growth factor-inducible 14 (Fn14), a member of the tumor necrosis factor (TNF) receptor superfamily, is expressed at high levels in migrating glioma cells in vitro and invading g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
293
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(318 citation statements)
references
References 36 publications
23
293
0
2
Order By: Relevance
“…4B). A few studies have indicated that Rho GTPases, especially Rac1 and Cdc42, interact with TWEAK receptor (31,32). However, we found that overexpression of a Rho GDP dissociation inhibitor protein that blocks the activation of RhoA, Rac1, and Cdc42 GTPases (33) did not affect either the activation of MMP-9 promoter or NF-B in myotubes (Fig.…”
Section: Tweak Increases Mmp-9 Production In C2c12 Myotubes and In Skmentioning
confidence: 68%
“…4B). A few studies have indicated that Rho GTPases, especially Rac1 and Cdc42, interact with TWEAK receptor (31,32). However, we found that overexpression of a Rho GDP dissociation inhibitor protein that blocks the activation of RhoA, Rac1, and Cdc42 GTPases (33) did not affect either the activation of MMP-9 promoter or NF-B in myotubes (Fig.…”
Section: Tweak Increases Mmp-9 Production In C2c12 Myotubes and In Skmentioning
confidence: 68%
“…For example, whereas both soluble TWEAK and memTWEAK are strong stimuli of the alternative NF-kB pathway, only memTWEAK also efficiently triggers the classical NF-kB pathway (24). Several members of the TNFR-associated factor (TRAF) family and Rac1 have been identified as Fn14-interacting molecules, but their relevance for defined aspects of Fn14 signal transduction is poorly understood (25)(26)(27). In molecular terms the best elucidated Fn14 signaling event is presumably TRAF2 recruitment and its relevance for alternative NFkB signaling (28).…”
mentioning
confidence: 99%
“…[19][20][21][22] NFκB is constitutively active in many cancers, including gliomas, [23][24][25] and aberrant regulation of NFκB signaling is involved in apoptosis evasion and tumor promotion. 26 In GBM, elevated NFκB signaling is associated with enhanced chemo-and radiation resistance in the mesenchymal subtype. 27 NFκB plays a fundamental role in inhibiting apoptosis by inducing anti-apoptotic factors, such as TRAF1 and cellular inhibitors of apoptosis proteins 1 and 2 (cIAP1/2).…”
Section: Lee Et Al Nfia-nfκb Feed-forward Loop In Gbmmentioning
confidence: 99%